Prevalence and patterns of chronic communicable and non-communicable diseases multimorbidity in sub-Saharan Africa: protocol for a systematic review - Mpho R Disang; David Weller; Christine Campbell (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background The burden of multimorbidity is rising globally. In sub-Saharan Africa (SSA), the growing prevalence of non-communicable diseases alongside the already existing high burden of chronic communicable diseases such as human immunodeficiency virus (HIV) presents a complex form of multimorbidity relative to patterns observed in high income countries. There is a gap in understanding the true burden of multimorbidity in SSA, in particular at interface of chronic communicable and non-communicable diseases (NCDs). The primary objective of this systematic review is to identify, evaluate and summarise the evidence on the prevalence and patterns of chronic communicable and NCDs multimorbidity in SSA. # Methods and analysis This protocol was developed in compliance with the Preferred Reporting Items for Systematic Review and Meta-Analyses Protocols (PRISMA-P) guidelines. A comprehensive search will be conducted on selected electronic databases including Medline, Embase, African Journals Online, based on a predefined search strategy for observational studies reporting primary data on multimorbidity from any country in the SSA region. Additionally, we will explore grey literature databases and check reference lists of included studies. Study selection, assessment of quality of included studies and data extraction will be carried out independently by two reviewers. A narrative synthesis will be conducted and meta-analysis will be carried out where applicable. # Conclusion The proposed systematic review will provide insights into the interface of chronic communicable diseases and NCDs in SSA. We expect this will provide additional insights into the true picture of multimorbidity in the region and assist policy makers to design appropriate prevention and management strategies. This review does not require ethical approval. Upon completion, it will be submitted for publication in peer-reviewed journals, and disseminated through relevant academic conferences. **Prospero registration**: CRD42020183539